Image Characteristicộng sự of Ruptured Arteriovenous Malformations of the Brain on the Multislice Computed Tomography - Ngoc, Doan Van; Anh Tuan, Tran; Thi Hong, Ho (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
This study describes the features of the image of the Ruptures Brain Arteriovenous Malformation (AVM) based on films of Multislide Computed Tomography (MSCT) at Bach Mai Hospital. The study used descriptive cross-sectional, prospective and retrospective method to analyze the MSCTs of 40 patients at the Center of Radiology, Bach Mai Hospital, from March 2019 to March 2020. The results show that the common age of the patients was <40 years old and the average age was 33.88 ± 16.27; the ratio of female/male was ≈ 1.11/1; 70% of the patients suffered from headache. On admission, 52.5% of the patients were conscious (glassgow 15 points), 30% of them lost consciousness (glassgow <13 points) and 17.5% were comatose; 47.5% had a syndrome of increased intracranial pressure; 22.5% with detected cerebral AVM but never treated; 77.5% with ruptured cerebral AVM in the upper floor of the cerebellum and 57.5% had it in the highly functional area; 67.5% with cerebral AVM ≤ 3cm in size. Feeding artery ≤ 3 stalks accounted for 85%, of which 1 stem accounted for the majority. Attached aneurysm accounted for 42.5%, mainly in AVM drive aneurysm (32.5%). Pure shallow drainage veins accounted for 50%. Brain parenchymal hemorrhage alone accounted for 60%. Brain parenchymal with ventricular and subarachnoid hemorrhage accounted for 37.5%. The small size hemorrhage volume ratio (<30 mm) and the average size (30-60 mm) accounted for the same percentage of 45%. According to the Spetzler - Martin classification, the cerebral ruptured venous malformation drive with low resolution (I-III) accounted for 85%. Overall, MSCT provides information to help guide the treatment of cerebral hemorrhage caused by cerebral AVM. Keywords: Arteriovenous malformation of the brain, ruptured cerebral arteriovenous malformations, Multislide Computed Tomography (MSCT). References [1] R. M. Friedlander, Clinical Practice, Arteriovenous Malformations of the Brain, N Engl J Med, Vol. 356, No. 26, 2007, pp. 2704-2712, https://doi.org/10.1056/nejmcp067192. [2] J. F. Yu, A. D. Nicholson, J. Nelson et al., Predictors of Intracranial Hemorrhage Volume and Distribution in Brain Arteriovenous Malformation, Vol. 24, No. 2, 2018, pp. 183-188, https://doi.org/10.1177/1591019917749819. [3] E. Shotar, M. Debarre, N. A. Sourour et al., Retrospective Study of Long-term Outcome after Brain Arteriovenous Malformation Rupture: the RAP Score, J Neurosurg, Vol. 128, No. 1, 2018, pp. 78-85, https://doi.org/10.3171/2016.9.jns161431. [4] P. M. Thong, N. H. An, The Initial Results of Treatment Mass the Brain Arteriovenous Malformation Rupture with Surgery in Combination with Embolization in Bach Mai Hospital; Vietnam Journal of Medicine, October, No. 1, 2017, pp. 51-56 (in Vietnames). [5] R. F. Speizler, N. A. Martin, A Proposed Grading System for Arteriovenous Malformations, J Neurosurg, Vol. 108, No. 1, 2008, pp. 186-193, https://doi.org/10.3171/jns/2008/108/01/0186 [6] M. Majumdar, L. A. Tan, M. Chen, Critical Assessment of the Morbidity Associated with Ruptured Cerebral Arteriovenous Malformations, J Neurointerv Surg, Vol. 8, No. 2, 2016, pp. 163-167, https://doi.org/10.1136/neurintsurg-2014-011517. [7] R. F. Spetzler, D. S. Kondziolka, R. T. Higashida et al., Comprehensive Management of Arteriovenous Malformation of the Brain and Spine, Cambridge University Press, 2015, pp. 78-85, https://doi.org/10.1080/01616412.1998.11740583 [8] R. Torné, R. A. Hernández, F. Arikan et al., Posterior Fossa Arteriovenous Malformations: Significance of Higher incidence of Bleeding and Hydrocephalus, Clin Neurol Neurosurg, Vol. 134, 2015, pp. 37-43, https://doi.org/10.1016/j.clineuro.2015.04.003.